INDEPENDENSI KOMISI PEMBERANTASAN KORUPSI: BENARKAH ADA? - Kartika Sasi Wahyuningrum; Hari Sutra Disemadi; Nyoman Serikat Putra Jaya (Refleksi Hukum: Jurnal Ilmu Hukum, 2020)
The importance of the independence of the Corruption Eradication Commission (KPK) is to accelerate the performance of the KPK itself. However, the enactment of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission (a revision of KPK Law) has concretely resulted in a weakening of the KPK institution. This doctrinal research uses a normative legal research method that is based on the statutory approach and conceptual approach in analytical descriptive analysis. The result of this study shows that the KPK has lost its independence by amending the Article 3 of the KPK Law. The weakening of the KPK can be seen through the formation of a supervisory body, and also the regulation of the State Civil Apparatus as the compulsory background of KPK staff resulting the KPK has limited space to perform as it is bound by the central command.